Peran Saluran Distribusi dan Pendidikan Petani terhadap Pendapatan Usahatani Cabai Merah Keriting di Kabupaten Kediri - Nina Lisanty; Wardatul Chamro'; Dafani Suprianto; Mochammad Agung Try Setyo; Dinda Putri Nurwiyanti (Journal of Agribusiness, Social and Economic, 2026)
This study aims to analyze differences in the income of curly red chili farmers based on the marketing channels they use and to examine the relationship between farmers’ education level and their income. The research was conducted in Kediri Regency across three major chili-producing subdistricts: Kepung, Puncu, and Ngancar, involving 45 farmer respondents. The approach used was descriptive quantitative with survey and case study methods. Data analysis employed the Kruskal-Wallis test to examine income differences based on marketing channels and the Spearman correlation test to determine the relationship between education and income. The results show a significant income difference based on marketing channels (p-value 0.038), with farmers who sell directly to consumers earning higher incomes than those selling to markets or middlemen. However, no significant relationship was found between the level of education and farmers’ income (p-value 0.946). These findings indicate that marketing strategy plays a crucial role in increasing farmers’ income, while formal education has not shown a direct influence in this context.